A composite flocculation precipitant and preparation method thereof
By calcining, acid etching and alkali leaching of hydrotalcite, and grafting with acrylamide, a composite flocculation precipitant was prepared, which solved the problem of poor adsorption of Fe2+ and Mn2+ ions in the prior art. , achieving efficient removal of these ions in acidic coal mine sewage.
Patent Information
- Application Number
- CN202411643105.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-18
AI Technical Summary
In the prior art, when treating acidic coal mine sewage, polyacrylamide flocculants do not have a specific adsorption effect on Fe2+ and Mn2+ ions, making it difficult for the residue of these ions in the sewage to meet the emission standards after treatment.
The water talc is treated by calcining, acid etching and alkali irrigation, and alkali irrigation are prepared and grafted with acrylamide through esterification to form a composite flocculation precipitant. The composite flocculation precipitant significantly improves the adsorption effect on Fe2+ and Mn2+ ions through the combined effect of micropore adsorption and charge adsorption.
It has achieved efficient adsorption of Fe2+ and Mn2+ ions in acid coal mine sewage, with removal rates of more than 98.8% and more than 95.6%, meeting sewage discharge standards and simplifying the treatment process.
Smart Images

Figure CN119143265B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of flocculants, and more specifically, to a composite flocculant precipitant and a preparation method thereof. Background Art
[0002] Acidic coal mine wastewater is a special type of industrial wastewater generated during coal mining and processing. Sulfide minerals such as pyrite are often found in coal mining products. Under the conditions of mining and exposure to air and water, the sulfur and other components in these sulfide minerals will gradually convert into sulfuric acid and other acidic substances. These acidic substances dissolve in coal mine wastewater, thus forming acidic coal mine wastewater. Acidic conditions will intensify the dissolution of high concentrations of metal ions in coal mines, among which Fe 2+ and Mn 2+ The dissolution of two metal ions can cause a series of problems.
[0003] High concentration of Fe in acidic coal mine drainage 2+ If it is discharged directly without treatment, it may cause eutrophication of water bodies and promote excessive reproduction of aquatic organisms such as algae, thus destroying the ecological balance of the water body. 2+ The interaction with acidic substances in acidic wastewater can also lead to an increase in soil acidification. 2+ As coal mine wastewater seeps out and accumulates, it will eventually cause excessive heavy metal content in the soil, poisoning crops and reducing the quality and safety of agricultural products. It is also transmitted through the food chain and easily causes manganese poisoning when ingested by humans, which reduces the immune system's ability and increases the risk of cancer. 2+ It easily combines with coal mine sediment to form black particles, which may block sewage pipes and equipment. 2+ and Fe 2+ ions are far higher than the allowable range in the national standard GB20426-2006 "Coal Industry Pollutant Emission Standard". Therefore, flocculation treatment is required before coal mine wastewater is discharged to reduce Fe 2+ , Mn 2+ mass concentration.
[0004] In the process of acidic coal mine wastewater treatment, flocculants are commonly used. Its mechanism of action is that the suspended particles and free metal ions in acidic coal mine wastewater aggregate and become larger or form flocs under the action of flocculants, which accelerates the coagulation of particles and finally separates the solid-liquid in the sewage pool. In the process of acidic coal mine wastewater treatment, suspended particles and metal ions in the coal mine can be adsorbed by adding flocculants into the sewage pool. Commonly used flocculants are inorganic flocculants based on ferric sulfate salts, and organic flocculants based on polyacrylamide. Among them, polyacrylamide flocculants are more commonly used in actual production due to their excellent flocculation ability, high sedimentation rate and strong adaptability to water treatment environments. Compared with inorganic flocculants of ferric sulfate salts, they have obvious advantages. However, polyacrylamide flocculants have a low affinity for Fe 2+ , Mn 2+ Plasma does not have a specific adsorption effect. After treatment, Fe 2+ , Mn 2+ There is still a high residual ion, which is difficult to meet the sewage discharge standard, so it is necessary to adsorb Fe 2+ , Mn 2+ The precipitant of ions is used in combination, and a composite flocculant is obtained by blending or the like.
[0005] The Chinese patent application document with publication number CN117430222A discloses a rapid flocculant and its preparation method and application. The waste fly ash is treated by alkali extraction, acid extraction, primary modification, secondary modification and then blended with polyacrylamide to prepare a rapid flocculant. The flocculant has good flocculation effect and can achieve Fe 2+ , Mn 2+ Effective adsorption of heavy metal ions.
[0006] In the above patent application document, the fly ash in the rapid flocculant needs to be modified through multiple steps to obtain Fe 2+ , Mn 2+ The strong adsorption effect of heavy metal ions such as Fe is complex to operate, and the use of polyacrylamide in a blended manner cannot guarantee the effective combination of polyacrylamide and other components. Therefore, a simple and easy-to-handle Fe adsorption 2+ , Mn 2+ And the demand for composite flocculants that effectively combine polyacrylamide still exists. Summary of the invention
[0007] In order to obtain a simple handling, adsorption of Fe 2+ , Mn 2+ And a composite flocculation precipitant of effectively combined polyacrylamide, the present application provides a composite flocculation precipitant and a preparation method thereof.
[0008] In a first aspect, the present application provides a method for preparing a composite flocculation precipitant, comprising the following steps:
[0009] (a) taking hydrotalcite and calcining it to obtain calcined hydrotalcite;
[0010] (b) mixing the calcined hydrotalcite with the mixed acid solution, filtering out the precipitate after treatment, and drying to obtain the acid-etched hydrotalcite;
[0011] (c) adding the acid-etched hydrotalcite to the mixed alkali solution, alkali leaching, filtering out the precipitate, washing with water, filtering out the precipitate, and drying the precipitate in an oven to obtain the alkali-leached hydrotalcite;
[0012] (d) dissolving acrylamide monomer and prepolymerizing to obtain a polyacrylamide solution, wherein the prepolymerization time of acrylamide monomer is 10-15 minutes, the temperature is 65° C., and ammonium persulfate is used as a prepolymerization initiator; dispersing alkali-soaked hydrotalcite, adding p-toluenesulfonic acid, heating, dripping the polyacrylamide solution to react, and then taking the precipitate, drying and crushing it, and grinding it to obtain a composite flocculation precipitant; the mass ratio of p-toluenesulfonic acid, alkali-soaked hydrotalcite and acrylamide monomer is (3-3.5):30:(45-55).
[0013] The composite flocculant prepared by adopting the above technical scheme can effectively remove Fe in acidic coal mine wastewater. 2+ , Mn 2+ Ions have a high adsorption effect. In the composite flocculant, the alkali-soaked hydrotalcite part is the specific adsorption of Fe 2+ , Mn 2+ ions. Hydrotalcite is a lamellar compound composed of aluminum-magnesium octahedrons, carbonates, and a small amount of anions and cations located in the skeleton. After a series of treatments, the alkali-soaked hydrotalcite can capture Fe in sewage through micropore adsorption and charge adsorption. 2+ , Mn 2+ ions. Through esterification reaction, the hydroxyl groups on the surface of alkali-soaked hydrotalcite combine with the carboxyl groups on the polyacrylamide molecular chain, thus obtaining a structure with alkali-soaked hydrotalcite as the center and multiple polyacrylamide chains grafted on the outside. The prepared composite flocculant helps Fe 2+ , Mn 2+ Ions and suspended particles can be precipitated, which can effectively reduce the Fe content in sewage. 2+ , Mn 2+ The effect of ions.
[0014] Preferably, in step (a), the calcination treatment is carried out by heating the temperature to 350-400°C at a rate of 5-8°C / min and then maintaining the temperature for 8-10 hours.
[0015] By adopting the above technical solution, during the slow heating process, CO3 2-It is converted into CO2, escaping the hydrotalcite layer structure system, and forming pores and vacancies in the hydrotalcite, constructing a Fe 2+ , Mn 2+ Ions have a larger adsorption area and more adsorption sites. The decomposition of hydrotalcite is significantly affected by temperature. When the temperature is below 500°C, hydrotalcite decomposes to produce water and CO2. When the calcination temperature is higher than 600°C, the structure of hydrotalcite is destroyed, and compounds such as magnesium oxide and aluminum oxide are generated, which greatly reduces the adsorption effect. Slow heating helps to slowly release CO2 and avoid damage to the layered structure of hydrotalcite. By regulating temperature and time, the adsorption effect of calcined hydrotalcite is the best.
[0016] Preferably, in step (b), the mixed acid solution is prepared by mixing dilute sulfuric acid with a molar concentration of 2-2.5 mol / L and dilute hydrochloric acid with a volume ratio of 1-1.5 mol / L at a ratio of 3:1.
[0017] By adopting the above technical solution, the prepared mixed acid solution is used to treat the calcined hydrotalcite, which can modify the pores produced after calcination, and help to obtain a more uniform and orderly pore structure. At the same time, the mixed acid treatment can promote the Al in the skeleton position of the hydrotalcite to 3+ Transformed into non-framework Al 3+ . Transformed non-framework Al 3+ In the 3+ As the solution dissolves, another part of Al 3+ Retained in the interlayers of hydrotalcite, and not easily taken away by weakly charged ion solutions through interlayer van der Waals forces and hydrogen bonds. 3+ It has a certain degree of substitution and can be used for Fe 2+ and Mn 2+ displacement adsorption.
[0018] Preferably, in step (b), the treatment temperature is set to 45-60° C., and stirring is continued for 0.5-1 h.
[0019] By adopting the above technical solution, the effect of mixed acid treatment is optimal.
[0020] Preferably, in step (c), the mixed alkali solution is prepared from methylamine, 25% by mass ammonia water, and benzalkonium chloride in a mass volume ratio of 10 g:150 mL:(1-2) g.
[0021] By adopting the above technical solution, the non-skeleton Al content between the hydrotalcite layers can be reduced. 3+ The precipitation loss of hydrotalcite is reduced and a certain hydroxyl structure is retained on the surface of hydrotalcite. After mixed acid treatment, the non-skeleton Al 3+Due to the limitation of interlayer spacing, weak bases with larger molecular volume, such as methylamine, are difficult to enter the interlayer of hydrotalcite and interact with Al due to interlayer repulsion and steric hindrance. 3+ The benzalkonium chloride in the mixed alkali solution is a cationic surfactant. On the one hand, it can disperse the acid-etched hydrotalcite in the mixed alkali solution. On the other hand, benzalkonium chloride is positively charged in the mixed alkali solution, which can inhibit the Al 3+ Dissolved from the interlayer structure of acid-etched hydrotalcite, and bound to OH in the alkali solution through positive and negative charge attraction and hydrogen bonding - . Reduced the non-framework Al in alkali-soaked hydrotalcite 3+ The prepared alkali-soaked hydrotalcite still has a high non-framework Al 3+ The retention amount.
[0022] Preferably, in step (c), the temperature of the alkali leaching treatment is set to 45-55° C., and the treatment is continued for 8-10 hours.
[0023] By adopting the above technical solution, more non-framework Al can be retained. 3+ . Non-skeleton Al2O3 between alkali-soaked hydrotalcite layers 3+ The dissolution amount of Al is related to temperature and time. Adjusting the alkali leaching time and temperature can reduce the non-framework Al 3+ The dissolution and subsequent influence on the adsorption effect of the composite flocculant precipitant.
[0024] Preferably, in the step (d), the prepolymerization time of acrylamide monomer is 10-15 min, the temperature is 65° C., and ammonium persulfate is used as a prepolymerization initiator.
[0025] By adopting the above technical scheme, acrylamide monomer is polymerized into short-chain polyacrylamide through prepolymerization treatment, and then grafted with alkali-soaked hydrotalcite through esterification reaction, the obtained composite flocculant precipitant has the best effect.
[0026] Preferably, in the step (d), the mass ratio of p-toluenesulfonic acid, alkali-soaked hydrotalcite and acrylamide monomer is (3-3.5):30:(45-55).
[0027] By adopting the above technical solution, the combination of alkali-soaked hydrotalcite and polyacrylamide in the prepared composite flocculant can achieve the best effect. In the composite flocculant, the alkali-soaked hydrotalcite mainly absorbs Fe 2 + , Mn 2+And increase the adsorption of two ions through pores and vacancies. Polyacrylamide mainly adsorbs suspended coal powder particles in acidic coal mine sewage. Finally, the adsorbed substances gradually form aggregates and naturally precipitate under the action of gravity. When the mass ratio of p-toluenesulfonic acid, alkali-soaked hydrotalcite and acrylamide monomer is in the range of (3-3.5):30:(45-55), the flocculation effect of the composite flocculant is the best.
[0028] In the second aspect, the present application prepares a composite flocculation precipitant through the above technical solution.
[0029] In summary, this application has the following beneficial effects:
[0030] 1. In the composite flocculant, alkali-impregnated hydrotalcite can play two adsorption effects. Adsorption is a combination of micropore adsorption and charge adsorption. On the one hand, after calcination, the carbonate in the hydrotalcite component is converted into CO2, leaving pores in the hydrotalcite. The pores are modified by acid, and the uniform pore structure enhances the micropore adsorption effect. On the other hand, the mixed acid treatment can 3+ Transformed into non-framework Al 3+ , non-framework Al 3+ These non-framework Al 3+ It can be removed by low charge transfer from Mn in acidic coal mine drainage 2+ and Fe 2+ Replacement, Mn 2+ and Fe 2+ They migrate into the hydrotalcite layer and are retained in defects and pores to achieve adsorption of the two ions.
[0031] 2. The carboxyl groups on the acrylamide molecular chain can be combined with the hydroxyl groups on the surface of the alkali-soaked hydrotalcite through esterification reaction. Through prepolymerization treatment, the polyacrylamide part of the composite flocculant can adsorb coal powder particles through the amide bond and other active groups on the molecule. With the help of esterification reaction, a structure with alkali-soaked hydrotalcite as the center and multiple polyacrylamide chains grafted on the outside is obtained. Through dual physical adsorption, the flocculation and precipitation speed of the composite flocculant is greatly enhanced.
[0032] 3. The composite flocculant was prepared by grafting polyacrylamide with alkali-soaked hydrotalcite, which can enhance the flocculation and precipitation ability of the composite flocculant. The prepared composite flocculant was used to treat the experimental sewage and the Fe 2+ The removal rate reached over 98.8%, Mn 2 +The removal rate reaches over 95.6%. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1: After the composite flocculation precipitant prepared in Examples 1-3 and Comparative Examples 1-2 of the present application was used to treat the test sewage, the residual Fe 2+ Mass concentration and Fe 2+ removal rate.
[0034] Figure 2 : After the composite flocculation precipitant prepared in Examples 1-3 and Comparative Examples 1-2 of the present application was used to treat the test sewage, the residual Mn in the sewage 2+ Mass concentration and Mn 2+ removal rate. DETAILED DESCRIPTION
[0035] Example 1
[0036] The preparation steps of the composite flocculation precipitant of this embodiment are as follows:
[0037] (a) 40 g of hydrotalcite was taken and placed in a muffle furnace for calcination. The temperature was raised at a rate of 5°C / min to 350°C, kept constant for 8 hours, and then cooled naturally at room temperature for 5 hours to obtain calcined hydrotalcite.
[0038] (b) The calcined hydrotalcite was placed in 100 mL of mixed acid solution, the magnetic stirring speed was controlled to be 150 rpm, the reaction temperature was controlled to be 45° C., stirring was continued for 0.5 h, and the precipitate was filtered to obtain the acid-etched hydrotalcite.
[0039] (c) The acid-etched hydrotalcite was added into 150 mL of mixed alkali solution, the magnetic stirring speed was controlled to be 50 rpm, the temperature was 45° C., the treatment was performed for 8 h, and then the precipitate was filtered and transferred into 200 mL of deionized water, soaked for 10 h, the precipitate was filtered and dried in an oven at 45° C. for 2 h to obtain the alkali-soaked hydrotalcite.
[0040] (d) 45 g of acrylamide monomer was dissolved in 100 mL of deionized water, and then 1.8 g of ammonium persulfate was added, and the reaction temperature was controlled to 65° C. After reacting for 10 min, a polyacrylamide solution was obtained. Then 30 g of alkali-soaked hydrotalcite was added to 200 mL of deionized water, and a dispersant of 1 g of sodium oleate, 0.2 g of sodium pyrophosphate, 0.8 g of sodium hexametaphosphate, and 3 g of p-toluenesulfonic acid, a catalyst for esterification reaction, were added. The system temperature was raised to 75° C., and 100 mL of polyacrylamide solution was added dropwise to the system at a rate of 15 mL / min. The magnetic stirring speed was 75 rpm and stirred for 10 min, and then the stirring speed was reduced to 50 rpm, and the reaction was continued for 2 h. The colloidal precipitate was filtered, dried in an oven, and crushed, and then ground using a ball mill and filtered using a 50 μm filter screen to obtain a composite flocculating precipitant.
[0041] Among them, hydrotalcite (average particle size 15μm, specific surface area 10m 2 / g) was provided by Xiamen Xindakang Inorganic Materials Co., Ltd. The mixed acid solution was prepared by mixing 2mol / L dilute sulfuric acid and 1mol / L dilute hydrochloric acid in a volume ratio of 3:1. The mixed alkali solution was prepared by mixing methylamine, 25% ammonia water, and benzalkonium chloride in a mass volume ratio of 10g:150mL:1g.
[0042] Example 2
[0043] The preparation steps of the composite flocculation precipitant of this embodiment are as follows:
[0044] (a) 45 g of hydrotalcite was taken and placed in a muffle furnace for calcination. The temperature was raised at a rate of 7°C / min to 375°C, kept constant for 9 hours, and then cooled naturally at room temperature for 5 hours to obtain calcined hydrotalcite.
[0045] (b) The calcined hydrotalcite was placed in 100 mL of mixed acid solution, the magnetic stirring speed was controlled to be 150 rpm, the reaction temperature was controlled to be 50° C., stirring was continued for 0.5 h, and the precipitate was filtered to obtain the acid-etched hydrotalcite.
[0046] (c) The acid-etched hydrotalcite was added into 150 mL of mixed alkali solution, and the magnetic stirring speed was controlled to be 50 rpm and the temperature was 50° C. The treatment was carried out for 10 h, and then the precipitate was filtered and transferred into 200 mL of deionized water, and soaked for 8 h. The precipitate was filtered and dried in an oven at 45° C. for 2 h to obtain the alkali-soaked hydrotalcite.
[0047] (d) 50 g of acrylamide monomer was dissolved in 100 mL of deionized water, and then 1.8 g of ammonium persulfate was added, and the reaction temperature was controlled to 65° C. After reacting for 10 min, a polyacrylamide solution was obtained. Then 30 g of alkali-soaked hydrotalcite was added to 200 mL of deionized water, and a dispersant of 1 g of sodium oleate, 0.2 g of sodium pyrophosphate, 0.8 g of sodium hexametaphosphate, and 3 g of p-toluenesulfonic acid, a catalyst for esterification reaction, were added. The system temperature was raised to 75° C., and 100 mL of polyacrylamide solution was added dropwise to the system at a rate of 15 mL / min. The magnetic stirring speed was 75 rpm and stirred for 10 min, and then the stirring speed was reduced to 50 rpm. The reaction was continued for 3 h, and the colloidal precipitate was filtered, dried in an oven, and then crushed, and then ground using a ball mill and filtered using a 50 μm filter screen to obtain a composite flocculating precipitant.
[0048] Among them, hydrotalcite (average particle size 15μm, specific surface area 10m 2 / g) was provided by Xiamen Xindakang Inorganic Materials Co., Ltd. The mixed acid solution was prepared by mixing 2.5mol / L dilute sulfuric acid and 1mol / L dilute hydrochloric acid in a volume ratio of 3:1. The mixed alkali solution was prepared by mixing methylamine, 25% ammonia water, and benzalkonium chloride in a mass volume ratio of 10g:150mL:1.5g.
[0049] Example 3
[0050] The preparation steps of the composite flocculation precipitant of this embodiment are as follows:
[0051] (a) 45 g of hydrotalcite was taken and placed in a muffle furnace for calcination. The temperature was raised at a rate of 8°C / min to 400°C, kept constant for 10 hours, and then naturally cooled at room temperature for 5 hours to obtain calcined hydrotalcite.
[0052] (b) The calcined hydrotalcite was placed in 100 mL of mixed acid solution, the magnetic stirring speed was controlled to be 200 rpm, the reaction temperature was controlled to be 60° C., the stirring was continued for 1 h, and the precipitate was filtered to obtain the acid-etched hydrotalcite.
[0053] (c) The acid-etched hydrotalcite was added into 150 mL of mixed alkali solution, the magnetic stirring speed was controlled to be 50 rpm, the temperature was 55° C., the treatment was carried out for 10 h, and then the precipitate was filtered and transferred into 200 mL of deionized water, soaked for 8 h, and then the precipitate was filtered and dried in an oven at 45° C. for 2 h to obtain the alkali-soaked hydrotalcite.
[0054] (d) 55 g of acrylamide monomer was dissolved in 100 mL of deionized water, and then 1.8 g of ammonium persulfate was added, the reaction temperature was controlled at 65° C., and the reaction was carried out for 15 min to obtain a polyacrylamide solution. Then 30 g of alkali-soaked hydrotalcite was added to 200 mL of deionized water, and a dispersant of 1.5 g of sodium oleate, 0.2 g of sodium pyrophosphate, 1 g of sodium hexametaphosphate, and 3.5 g of p-toluenesulfonic acid as a catalyst for the esterification reaction were added. The system temperature was raised to 80° C., and 100 mL of the polyacrylamide solution was added dropwise to the system at a rate of 15 mL / min. The magnetic stirring speed was 75 rpm and the mixture was stirred and mixed for 10 min, and then the stirring speed was reduced to 50 rpm. The reaction was continued for 3 h, and the colloidal precipitate was filtered and obtained. After drying in an oven, the precipitate was crushed, and then ground using a ball mill and filtered using a 50 μm filter screen to obtain a composite flocculating precipitant.
[0055] Among them, hydrotalcite (average particle size 15μm, specific surface area 10m 2 / g) was provided by Xiamen Xindakang Inorganic Materials Co., Ltd. The mixed acid solution was prepared by mixing 2.5mol / L dilute sulfuric acid and 1.5mol / L dilute hydrochloric acid in a volume ratio of 3:1. The mixed alkali solution was prepared by mixing methylamine, 25% ammonia water, and benzalkonium chloride in a mass volume ratio of 10g:150mL:2g.
[0056] Comparative Example 1
[0057] The only difference between this comparative example and Example 3 is that 2 mol / L dilute sulfuric acid is used in step (b) instead of the mixed acid solution, and the rest is the same as Example 3.
[0058] Comparative Example 2
[0059] The only difference between this comparative example and Example 3 is that p-toluenesulfonic acid, the esterification reaction catalyst, is not added in step (d), and the rest is the same as Example 3.
[0060] Performance testing
[0061] Preparation of experimental sewage: 0.54gMnCl2·4H2O, 4.46gFeSO4·7H2O, 15g coal powder, 10L deionized water, 2g dispersant polyethylene glycol, adjust the solution pH to 4, and prepare Mn 2+ The concentration is 15 mg / L, Fe 2+ The concentration of the mixed solution is 90 mg / L. The dynamic adsorption method is used to control the magnetic stirring speed to 100 rpm, and the stirring is continued to simulate the environment of acidic coal mine sewage in the sewage treatment tank.
[0062] Preparation of flocculation precipitant dilution: 0.5 g of the composite flocculation precipitant prepared in Example 1-3 and Comparative Example 1-2 were respectively mixed with deionized water to prepare a mixed solution with a composite flocculation precipitant mass fraction of 0.1%, to obtain a flocculation precipitant dilution.
[0063] Experimental operation steps: According to the usage of 80mg / L composite flocculant, the flocculant dilution was added to the test sewage for testing, and the total suspended solids, total iron and total manganese residues were measured. Then lime powder was added to the sewage to adjust the pH, and after standing for 2 hours, the sewage sample was taken for pH testing.
[0064] Among them, coal powder (particle size ≤ 100 mesh, slag characteristics level 5-6) is provided by Qufu Hongyun Casting Materials Factory.
[0065] Table 1 Performance test method table of Examples 1-3 and Comparative Examples 1-2
[0066]
[0067] pH Test
[0068] Referring to the operation and test methods of GB20426-2006 and GB / T6920-1986, the glass electrode method was used to test the pH of the treated wastewater.
[0069] Total suspended solids test
[0070] Referring to the operation and test methods of GB20426-2006 and GB / T11901-1989, the total suspended volume of the test sewage before and after was tested using the weight method.
[0071] Fe 2+ Content test
[0072] Take 250 mL of wastewater samples without flocculation treatment and after flocculation treatment, and use o-phenanthroline spectrophotometry to determine the residual Fe in the solution. 2+ Mass concentration, calculate the composite flocculant precipitation to Fe 2+ The removal rate W.
[0073] Removal rate calculation formula:
[0074]
[0075] W:Fe 2+ Removal rate, (%);
[0076] :Initial Fe in sewage 2+ Ion concentration, (g / mL);
[0077] :Fe in treated wastewater 2+ Ion concentration, (g / mL).
[0078] Mn 2+ Content test
[0079] Take 250 mL of wastewater samples without flocculation treatment and after flocculation treatment, and use potassium periodate spectrophotometry to determine the residual Mn in the solution. 2+ Mass concentration, calculate the composite flocculant precipitation agent to Mn 2+ The removal rate N.
[0080] Removal rate calculation formula:
[0081]
[0082] :Mn 2+ Removal rate, (%);
[0083] :Initial Mn in sewage 2+ Ion concentration, (g / mL);
[0084] : Mn in treated wastewater 2+ Ion concentration, (g / mL).
[0085] Table 2 Performance test results of Examples 1-3 and Comparative Examples 1-2
[0086] Analyze Examples 1-3 and Comparative 1-2 and combine Table 2 and Figure 1 It can be seen that the composite flocculant prepared in the embodiment has an effect on Fe 2+In the three embodiments, the composite flocculation precipitant prepared in Example 2 has an effective adsorption effect on Fe 2+ The removal rate of composite flocculant is the highest. 2+ The removal rate can reach 99.19%, which is higher than that of the composite flocculant prepared in Comparative Example 1-2.
[0087] Analyze Examples 1-3 and Comparative 1-2 and combine Table 2 and Figure 2 It can be seen that the composite flocculation precipitant prepared in the embodiment has an effective effect on Mn 2+ In the three embodiments, the composite flocculation precipitant prepared in Example 2 has an effective adsorption effect on Mn 2+ The removal rate of composite flocculant is the highest for Mn 2+ The removal rate can reach 98.2%, and the removal effect is significantly higher than that of the composite flocculant prepared in Comparative Example 1-2.
[0088] Analysis of Examples 1-3 and Comparative Examples 1-2 and combined with Table 2 shows that by comparing the acid mine wastewater discharge standard values with the pH and Fe in the wastewater after the test treatment, 2+ , Mn 2+ As well as the total suspended solids content, the test wastewater can meet the sewage discharge standards after flocculation treatment.
[0089] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A method for preparing a composite flocculation precipitant, characterized in that: The steps include: (a) taking hydrotalcite and calcining it to obtain calcined hydrotalcite; (b) mixing the calcined hydrotalcite with the mixed acid solution, filtering out the precipitate after treatment, and drying to obtain the acid-etched hydrotalcite; (c) adding the acid-etched hydrotalcite to a mixed alkali solution, alkali-leaching the solution, filtering the precipitate, washing the precipitate with water, filtering the precipitate, and drying the precipitate in an oven to obtain the alkali-leached hydrotalcite; the mixed alkali solution is prepared from methylamine, 25% ammonia water by mass, and benzalkonium chloride in a mass volume ratio of 10 g:150 mL:(1-2) g; (d) dissolving acrylamide monomer and prepolymerizing to obtain a polyacrylamide solution, wherein the prepolymerization time of acrylamide monomer is 10-15 minutes, the temperature is 65° C., and ammonium persulfate is used as a prepolymerization initiator; dispersing alkali-soaked hydrotalcite, adding p-toluenesulfonic acid, heating, dripping the polyacrylamide solution to react, and then taking the precipitate, drying and crushing it, and grinding it to obtain a composite flocculation precipitant; the mass ratio of p-toluenesulfonic acid, alkali-soaked hydrotalcite and acrylamide monomer is (3-3.5):30:(45-55).
2. The method for preparing a composite flocculation precipitant according to claim 1, characterized in that: In the step (a), the calcination treatment is carried out by heating the temperature to 350-400°C at a rate of 5-8°C / min and then maintaining the temperature for 8-10 hours.
3. The method for preparing a composite flocculation precipitant according to claim 1, characterized in that: In the step (b), the mixed acid solution is prepared by mixing dilute sulfuric acid with a molar concentration of 2-2.5 mol / L and dilute hydrochloric acid with a volume ratio of 1-1.5 mol / L at 3:
1.
4. The method for preparing a composite flocculation precipitant according to claim 1, characterized in that: In the step (b), the treatment temperature is set to 45-60° C., and stirring is continued for 0.5-1 h.
5. The method for preparing a composite flocculation precipitant according to claim 1, characterized in that: In the step (c), the temperature of the alkali leaching treatment is set to 45-55° C., and the treatment is continued for 8-10 hours.
6. A composite flocculant precipitant prepared by the preparation method according to any one of claims 1 to 5.
Citation Information
Patent Citations
Rapid flocculant as well as preparation method and application thereof
CN117430222A
Method and composition for clarifying waste water
CN1132183A